Experimental characterization of the thermodynamic cycle of a self-oscillating fluidic heat engine (SOFHE) for thermal energy harvesting. (15th April 2022) - Karami, N.; Tessier-Poirier, A.; Nikkhah, Alihossein; Léveillé, E.; Monin, T.; Formosa, F.; Fréchette, L.G.
Highlights: Harvestable energy by SOFHE is equal to work by thermodynamic cycle minus friction loss. Generating maximum mechanical power density with a magnitude of mW. Bell shape curve for power density shows an optimal load. Increasing power density by increasing heat source temperature and adding wicking structures. Decreasing the liquid length yields higher power density for miniaturization. Abstract: We experimentally studied the thermodynamic cycle of a single branch pulsating heat pipe (SB-PHP) to show its potential as a Self-Oscillating Fluidic Heat Engine (SOFHE) capable of generating electric power from heat. The engine consists of a vapor bubble trapped by an oscillating liquid plug acting like a piston in a tube of mm-scale diameter. Pressure build-up in the vapor bubble can provide net mechanical work that can then be converted into electrical energy by coupling the liquid plug motion to an electro-mechanical transducer. The transducer can be represented, in a first approach, as a dissipative mechanical load acting on the engine that will tend to reduce the oscillations. Unlike a standard pulsating heat pipe, we aim here at maximizing the mechanical work produced rather than the heat transfer rate. However, it is still unclear how the unique thermodynamic cycle of the oscillating vapor bubble-liquid plug behaves under a mechanical load and what effects the design parameters have on the generated mechanical power. Thereby, we conducted experiments to measure the pressure, displacement and operating frequency from which the generated mechanical work and power can be evaluated under varying loads. We observed a maximum mechanical power density with a magnitude of 0.5 mW/cm 3 at an optimal load and a cycle efficiency ratio with respect to Carnot of 30%. We also studied the effect of the heat source operating temperature and two design parameters on the mechanical power density. It was shown that the mechanical power density can be improved by increasing the heat source temperature, adding wicking structures inside the tube as well as decreasing the liquid length. Finally, we found that the mechanical power density of the SOFHE makes it a promising technology to power a wide range of low-power wireless sensors (requiring 10′s of microwatts) for the Internet of Things (IoT), if designed with adequate electro-mechanical coupling.